Adipose tissue from oesophageal adenocarcinoma patients is differentially affected by chemotherapy and chemoradiotherapy regimens altering immune cell phenotype and cancer cell metabolism - Fiona O'Connell; Eimear Mylod; Noel E. Donlon; Maria Davern; Christine Butler; Niamh O'Connor; Meghana S. Menon; Claire L. Donohoe; Narayanasamy Ravi; Derek G. Doherty; Margaret R. Dunne; John V. Reynolds; et al. (Translational Oncology)
Oesophageal adenocarcinoma (OAC) is a poor prognosis cancer with limited responses to standard of care treatments including chemotherapy and chemoradiotherapy. OAC has one of the strongest associations with obesity, its anatomical location surrounded by visceral adipose tissue has been postulated to intensify this association. Adipose tissue is a regulatory organ with many unknown downstream functions, including its direct response to chemotherapy and radiotherapy. To elucidate the role of visceral adipose tissue in this disease state, metabolic and secreted pro-inflammatory cytokines analysis was conducted on human ex-vivo adipose tissue explants following exposure to FLOT-chemotherapy and CROSS-chemoradiotherapy. To assess how these complex treated microenvironments impact cancer cell metabolism, dendritic cell, and macrophage phenotype, mitochondrial bioenergetics and surface markers expression were examined using seahorse technology and flow cytometry respectively. This study observed that chemotherapy and chemoradiotherapy differentially alter adipose tissue metabolism and secretome, with chemoradiotherapy increasing pro-inflammatory associated mediators (p < 0.05). The chemoradiotherapy-treated adipose secretome increased cancer cell spare respiratory capacity and dendritic cell adhesion markers (p < 0.05). In contrast, the chemotherapy-treated adipose microenvironment enhanced mitochondrial dysfunction in cancer cells, increasing their reliance on glycolysis and enhancing pro-inflammatory marker expression on LPS-primed macrophages (p < 0.05). This study for the first time demonstrates how adipose tissue, and its microenvironment can be significantly impacted by chemotherapy and chemoradiotherapy. These alterations in the adipose secretome in response to therapeutic regimens elicited distinct effects on immune cell phenotype and cancer cells metabolism, raising the question, does the wider tumour microenvironment including the adipose milieu mitigate the efficacy of current treatments.